War by Numbers : Understanding Conventional Combat - Lawrence, Christopher A. (Book collections on Project MUSE., 2017)
"War by Numbers assesses the nature of conventional warfare through the analysis of historical combat. Christopher A. Lawrence establishes what we know about conventional combat and why we know it. By demonstrating the impact a variety of factors have on combat he moves such analysis beyond the work of Carl von Clausewitz and into modern data and interpretation. Using vast data sets, Lawrence examines force ratios, the human factor in case studies from World War II and beyond, the combat value of superior situational awareness, and the effects of dispersion, among other elements. Lawrence challenges existing interpretations of conventional warfare and shows how such combat should be conducted in the future, simultaneously broadening our understanding of what it means to fight wars by the numbers"--Provided by publisher